A New Thermo‐, pH‐ and CO2‐Responsive Fluorescent Four‐Arm Star Polymer with Aggregation‐Induced Emission for Long‐Term Cellular Tracing. Issue 6 (16th April 2018) - Guan, Xiaolin; Meng, Li; Jin, Qijun; Lu, Baocui; Chen, Yanbin; Li, Zhifei; Wang, Lin; Lai, Shoujun; Lei, Ziqiang
Abstract: Development of fluorescent bioprobes for long‐term cell tracking is of great importance to monitor the processes of genesis, development, invasion, and metastasis of cancerous cells. Herein, a new multistimuli‐responsive star polymer of tetraphenylethene‐graft‐tetra‐poly[ N ‐[2‐(diethylamino)‐ethyl]acrylamide] (TPE‐tetraPDEAEAM) with aggregation‐induced emission (AIE) effect for tracing live cells over a long period of time is synthesized by atom transfer radical polymerization using TPE derivative as initiator. TPE‐tetraPDEAEAM gives both lower critical solution temperature and fluorescence responses to the stimulus of the temperature, pH, and CO2 by combining the thermoresponsive and pH/CO2 ‐responsive moieties of the diethylamino and acrylamide groups. The AIE‐active TPE‐tetraPDEAEAM has the advantages of very low cytotoxicity, efficient cellular uptake, and strong fluorescence of polymer‐treated cells, which ensure its good performance in long‐term cell tracing. This facile tracking of HeLa cells for as long as nine passages exhibits superior performance in long‐term cell tracing as compared with some commercial cell tracing probes. Abstract : In this work, a new multistimuli‐responsive star polymer tetraphenylethene‐graft‐tetra‐poly[ N ‐[2‐(diethylamino)‐ethyl]‐acrylamide] (TPE‐tetraPDEAEAM) is synthesized by atom transfer radical polymerization using a TPE‐initiator. Aggregation‐induced emission‐active TPE‐tetraPDEAEAM gives both lower critical solution temperature and fluorescence responses to the stimulus of the temperature, pH, and CO2 . More interestingly, TPE‐tetraPDEAEAM exhibits superior performance in long‐term cell tracing as compared with some commercial cell tracing probes.